SECURE MULTI CLOUD STORAGE APPROACH FOR MULTICLOUD ENVIRONMENTS USING FOG COMPUTING - R, Janaki; Prathap S; R, Raman; Tony Wilson I; Yuvaraj J (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The use of cloud computing is rapidly increasing in many organizations. Cloud computing offers many advantages in terms of easy access to data at low cost. In a cloud computing environment, ensuring the security of cloud computing is a key element. Users typically store sensitive information on cloud storage providers, which may be unreliable. Since a single point of attack cannot expose all information, distributing data across different cloud storage providers (CSPs) automatically provides users with a level of control over data exfiltration. The study focuses on how to make key renewals as transparent as possible to customers, using key renewal outsourcing and a method called cloud storage auditing, which verifies it according to the Protection Security Algorithm (PSA). The propose system minimizes the burden of rekeying on the client side securely outsourced to the authorized party. a client uploads a new file to the cloud, it only needs to download the encryption private key from the TPA. In addition, our design also provides the user side with the ability to further verify the validity of the encryption private key provided by the PSA. All of these notable features have been carefully designed to make the entire audit process as transparent as possible to clients with significant risk resistance. Cloud computing formalizes this paradigm's definition and security model. Good safety performance simulations demonstrate that the detailed design instantiation is safe and efficient.